Reliance on double pedicle TRAM flap technique in breast reconstruction based on mammographic evidence - Fuat Yüksel; Emir Silit; Bahattin Çeliköz (Indian Journal of Plastic Surgery)
Breast reconstruction is now a part of the overall treatment of breast cancer. Its main drawback is rather the suspicion to conceal any probable recurrence. Fat necrosis is a particularly important finding because it can be mistaken for a local recurrence. Alternatively, local recurrences may be dismissed as areas of fat necrosis. Fat necrosis is a relatively minor complication of TRAM flap breast reconstruction but one that can induce anxiety, expense, and inconvenience for patients and concerns about tumor recurrence. The techniques selected for reconstruction must carry the least risks for these awful complications.